PHYSICAL AND MECHANICAL CHARACTERISTICS OF EDIBLE FILM BASED ON CASSAVA PEEL STARCH - Ahmad Wira Wasistha; Muhammad Reza Sukma Dika; Annisa’ Sakina Aulia; Norazkya Mutiara Samudra; Desiana Nuriza Putri (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2021)
Cassava peel is an agro-industrial waste that is not used or not recycled. Based on the carbohydrate content of cassava peel, which is 50% of the weight of the peel, so that the cassava peel can be used as an ingredient for making edible films. Edible film is a thin layer made of natural ingredients that are safe for consumption. The biodegradable nature and can be used in this edible makes edibles used because they can be an alternative to synthetic plastics and are environmentally friendly. The purpose of this study was to determine the physical properties and mechanisms of the edible film of cassava peel starch. This study used a simple randomized block design (RBD) with 3 levels, namely A1(2%), A2(4%), A3(6%) with 3 replications. Research data on cassava peel characteristics showed water content (14.62%), starch content (73.29%), amylose content (21.02%), amylopectin content (52.27%), and HCN content (7.01%). %). The results of the edible physical and mechanical properties showed the value of tensile strength 0.08 – 0.37 Mpa, thickness 0.09 – 0.17 mm, WVTR 0.26 – 0.39 g/m2/Day, and elongation 31, 86 – 56.43%.